A Study on Quantification of Homogenizing Treatment for Al-Mg-Si Alloy AA 6063 - Kelesoglu, Erguen (CARL HANSER VERLAG, 2010)
Homogenization of aluminum extrusion billets facilitates extrusion and improves product quality. In this work, a parameter has been developed that defines the homogenization level of AA6063 extrusion billets. The insoluble alpha-AlFeSi and beta-AlFeSi phases have been experimentally determined by evaluating the length/width ratio of the AlFeSi intermetallic in the microstructure. Using this identification, the area fraction of each phase has been measured. The area fraction of the beta-AlFeSi phase in the cast structure is over 65%. In the well-homogenized sample, the beta-AlFeSi area fraction decreases to values lower than 20%, while the alpha-AlFeSi phase ratio increases to over 80%. As the alpha-AlFeSi percentage in the structure increases, the elongation of the samples steadily increases, from 1% to 24%. Based on the ratio of alpha-AlFeSi to the entire intermetallic phase, we propose six different homogenization levels. The proposed indexing can be used to define the homogenization state of the billet, regardless of the homogenization temperature and time. The index numbers exhibit a good correlation with the deformation potential of the samples.
Keywords: MICROSTRUCTURE; FE; Materials Science